Patient preferences and experiences regarding thrombopoietin-receptor agonists for immune thrombocytopenia in the United Kingdom and Ireland (TRAPeze UK & IE study). Issue 1 (1st January 2021) - McDonald, Vickie; Newland, Adrian; Morgan, Mervyn; Wilson, Koo; Nazir, Jameel; Maguire, Peter; Geldman, Emma; Wynne, Tammy
ABSTRACT: Objectives: To establish the experiences with and preferences towards existing thrombopoietin-receptor agonist (TPO-RA) treatments of individuals with immune thrombocytopenia (ITP) in the UK and Ireland, based on treatment attributes. Methods: Responses from UK and Ireland individuals with ITP were collected in a pan-European online survey (TRAPeze, [Thrombopoietin-Receptor Agonist Patient experience survey]) from 18 September 2020 to 18 February 2021. TRAPeze was a survey of treatment preference regarding TPO-RAs (using a discrete choice experiment design), participant demographics, disease characteristics, treatment history, overall satisfaction with therapy, direct healthcare resource utilization and wider social impact. Results: The survey was completed by 32 UK respondents. Characteristics with the greatest influence on preference towards TPO-RA treatments were method of administration (odds ratio (OR) 5.6, 95% confidence interval (CI) 3.2–10.1) and drug-food interactions (OR 3.2, 95% CI 1.8–5.7). Particularly, participants were more likely to select an oral tablet over a subcutaneous injection (OR 7.4, 95% CI 3.6–15.1) and a treatment without food restrictions rather than with food restrictions (OR 3.6, 95% CI 1.8–6.8). Conclusion: This is the first study to quantify the preference of individuals with ITP towards TPO-RA treatment attributes and demonstrates preference for orally administered treatments, without drug-food interactions.